Hybrydy wciąż młode… - Legeżyńska, Anna (Przestrzenie Teorii, 2013)
This is a review of Paweł Majerski’s book Hybrydy. O „młodej poezji” z lat sześćdziesiątych (Wydawnictwo Uniwersytetu Śląskiego, Katowice 2011) [Hybrids. About “young poets” of the 1960s]. The author discusses the history of this literary group and interprets the literary output of some poets. This book is very important for Polish post-war literary history because it restores the importance of the generation, which was discredited by younger writers of the so-called “generation of 1968”.